Association of Perioperative Whole Blood Transfusion with Troponin I Release after Off-Pump Coronary Artery Bypass Surgery - Begum, Mahfuza; Sarker, Rampada; Hasan, Md Kamrul; Zaman, Tanveer; Jahan, Hosne; Hussain, Sabrina Sharmin; Adhikary, Asit Baran (University Heart Journal, 2018)
Background: Increased postoperative levels of Troponin I (TnI) after Off-pump Coronary Artery Bypass Grafting (OPCABG) surgery can often be observed in patients in the absence of significant perioperative hemodynamic instability or any evident intra-operative technical problems or signs of graft failure. A study undertaken by Biancari and his collegues (2012) found that Red Blood Cell transfusion was associated with increased TnI release after elective OPCABG1. Serum TnI level is an established indicator of myocardial injury. This prospective observational study was conducted in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases and Department of Cardiac Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from January 2015 to December 2016 to assess whether intraoperative and immediate postoperative Whole Blood Transfusion resulted in increased release of TnI after isolated OPCABG operation. Materials & Methods: A total of 40 patients (34 males and 6 females) undergoing OPCABG were consecutively enrolled in the study, 20 patients in the transfusion recipient group and 20 patients in the non-transfusion recipient group. The groups were compared for pre-operative baseline characteristics and co-morbidities, per-operative techniques and events, and postoperative or end-point variables including Postoperative TnI level measured 12 hours at the end of surgery and a number of other clinical outcomes. Results: Both transfusion recipient and non-transfusion recipient groups had statistically indifferent baseline characteristics, co-morbidity counts, operative techniques and operative events. No significant difference (p = 1.000) was noted in case-counts with increased Postoperative TnI level between the groups (85% in the transfusion recipient group versus 90% in the non-transfusion recipient group). All other clinical outcomes were also found to be similarly distributed with no statistical difference between the groups. Conclusion: In contrast to Red Blood Cell transfusion in several other studies, perioperative Whole Blood transfusion was not associated with increased postoperative Troponin I (TnI) release after isolated offpump coronary artery bypass grafting (OPCABG) operation. University Heart Journal Vol. 13, No. 2, July 2017; 55-58